El uso de la información judicia - Gessner, Volkmar (Oñati Socio-Legal Series, 2011)
Although empirical data on courts and judicial systems are frequently discussed in comparative as well as in economic and sociological studies it turns out that the actors of court reform projects such as judges, law professors, civil servants or politicians don’t make adequate use of them. The paper posits that the reasons are of a structural nature which assigns different social roles to those actors. One solution may be the creation of specialized research institutions. A much wider, more pluralistic and more democratic approach is internet transparency which gives access to all kinds of documents including court statistics and empiricial studies to the general public. In order to get an impression of the practice of court transparency a large number of court websites were visited and ranged according to their content. The top positions reached only some anglosaxon and us-american websites which offer legal, economic, organizational as well as empirical information and even offer assistance for using the data. Those efforts may still not reach their purpose if the information isn’t recalled. In order to measure the actual use of the contents of court websites it is insufficient to count the visits. One needs to know more about the concerns leading to those visits. Fortunately, we have found one (Mexican) website which offers information about the visitors: their concerns, their “story” and even their names and (sometimes) place of residence. These petititions have been carefully evaluated and are discussed in the article. It turns out that empirical information about courts and judicial practices is in high demand. Internet transparency seems to be successful although the best forms of offering information still have to be found.